2018
DOI: 10.1002/ece3.4490
|View full text |Cite
|
Sign up to set email alerts
|

Limited introgression supports division of giraffe into four species

Abstract: All giraffe (Giraffa) were previously assigned to a single species (G. camelopardalis) and nine subspecies. However, multi‐locus analyses of all subspecies have shown that there are four genetically distinct clades and suggest four giraffe species. This conclusion might not be fully accepted due to limited data and lack of explicit gene flow analyses. Here, we present an extended study based on 21 independent nuclear loci from 137 individuals. Explicit gene flow analyses identify less than one migrant per gene… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
41
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(49 citation statements)
references
References 51 publications
7
41
0
Order By: Relevance
“…Giraffe ( Giraffa spp. ; Winter, Fennessy, & Janke, ) are reported to be particularly vulnerable while drinking due to their body posture with splayed or bent legs (Seeber, Ciofolo, & Ganswindt, ; Valeix, Fritz, et al, ). As a result, drinking events of giraffe are often preceded by longer scanning periods and increased vigilance (Seeber et al, ) as well as an avoidance of waterholes when lions are in the vicinity (Valeix, Fritz, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Giraffe ( Giraffa spp. ; Winter, Fennessy, & Janke, ) are reported to be particularly vulnerable while drinking due to their body posture with splayed or bent legs (Seeber, Ciofolo, & Ganswindt, ; Valeix, Fritz, et al, ). As a result, drinking events of giraffe are often preceded by longer scanning periods and increased vigilance (Seeber et al, ) as well as an avoidance of waterholes when lions are in the vicinity (Valeix, Fritz, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the process of lineage sorting under plausible demographic and selection models was not considered, nor their influence in the context of the limited number of markers used. A follow-up study using a larger set of nuclear markers has since been carried out, which confirms that gene-flow between the four proposed species is very low (Winter et al 2018). However, it appears that in this situation the argument is predominantly of an ontological nature, and so may not have run its course yet.…”
Section: Giraffementioning
confidence: 60%
“…Program: Heled and Drummond [19]; Individual assignment of alleles: present study Bayesian method implemented in BEAST 2 [65] based on the MSC model G. tippelskirchi (N.B. the subspecies camelopardalis, antiquorum and thornicrofti were not included in their study); whereas Fennessy et al [38] and Winter et al [12] suggested a division into four species, i.e., G. camelopardalis, G. giraffa, G. reticulata and G. tippelskirchi, based on multi-locus analyses of 7 and 21 nuclear introns, respectively. However, the four-species hypothesis proposed by Fennessy et al [38] has previously elicited concerns and controversy (see Bercovitch et al [39]).…”
Section: Msc + Pmentioning
confidence: 99%
“…Indeed, the maternal inheritance of the mtDNA genome can be misleading for species delimitation in mammals, because females and males have usually different dispersal behaviours (female philopatry versus male dispersal) [5,6], and because interspecific hybrid females are generally fertile, whereas hybrid males are often sterile (Haldane's rule), facilitating mitochondrial introgression between closely related species [7][8][9]. To overcome these limitations, most recent taxonomic studies dealing with the delimitation between cryptic mammal species have focused on multi-locus datasets [10][11][12], as the use of multiple independent DNA markers has been shown to provide a strong and reliable signal for deciphering relationships among closely related taxa [13,14]. However, interpreting the results from multi-locus datasets can be difficult, especially when the DNA markers show low genetic variation or conflicting relationships between them.…”
Section: Introductionmentioning
confidence: 99%